Pengembangan sistem informasi pelaporan Evaluasi Dosen Oleh Mahasiswa (EDOM) Universitas Negeri Makassar - Sapto Haryoko; Ansari Saleh Ahmar; Herman Herman (Seminar Nasional LP2M UNM, 2019)
The purpose of this study is to develop application reporting results of lecturer evaluations by students. The output of this research is the application of reporting results of lecturer evaluations by students in the form of recapitulation of the results of lecture evaluations, recap per faculty and university recapitulation. This research will be carried out within the scope of Makassar State University. This research is a development research that refers to the ADDIE model (Analysis-Design-Develop-Implement-Evaluate). The first stage of this research was to analyze the results of the lecturer evaluation instrument by students (EDOM) which had been filled in by students in the 2017-2018 odd semester, after that, the EDOM reporting information system application was developed, in the same year testing and product evaluation will be carried out later in use in reporting the results of lecturer evaluations by students in the following semester